“I can't be gay, I can't be trans here”: institutionalised hetero-, cisnormativity in Singapore secondary schools and LGBTQ+ identities - Gan, Amelia Qiao Hui (Nanyang Technological University, 2024)
In a predominantly conservative Singapore where heterosexuality and cisgenderism along a gender binary remain the social norms, secondary education and schools have emerged as highly contested and problematised yet largely uninvestigated sites of institutionalised heteronormativity/cisnormativity (IHC) that render Lesbian, Gay, Bisexual, Transgender, Queer/Questioning and other (LGBTQ+) individuals locally invisible and unseen, silenced and unheard, ostracised and unspoken about during their formative years. Through semi-structured interviews, this study aims to better understand how LGBTQ+ individuals have experienced IHC in their secondary education, and how such experiences have influenced their sense of gender and sexual self-identities during their formative years. The study’s findings highlight that LGBTQ+ individuals experience IHC in schools as a form of biopower that enforces conformity of their bodily performances and identities along hetero- and cisnormative lines via various ways on multiple levels, contributing to highly adverse impacts on LGBTQ+ individuals’ sense of gender and sexual identities.